Dinamika Madrasah dan Sekolah Muhammadiyah di Era Transisi Kebijakan Kurikulum - Abdul Hopid; Wantini; Fitri Andriani; Sutipyo; Abdunrorma Sama Alee (At Turots: Jurnal Pendidikan Islam, 2024)
This research reveals and describes the dynamics of madrasas and Muhammadiyah schools in the era of curriculum policy transition, where curriculum changes in Indonesia have a serious impact on educational institutions. The era of policy transition causes upheaval and dynamics that are not simple. The type of research used is descriptive research. Data was obtained through questionnaires and interviews as more in-depth information. The respondents in this study were 31 educators in madrasas and Muhammadiyah schools in Yogyakarta City, spread across seven educational institutions starting from elementary (SD), middle school (SMP), and high school (SMA). The results of the research show that there are dynamics in madrasas and Muhammadiyah schools in the city of Yogyakarta. First, the implementation of 2 types of curriculum (K-13 and the Independent Learning Curriculum). Second, there is a level of concern among educators regarding student achievement and achievements. Third, even though there are quite big concerns, personally, the majority of educationists accept the implementation of the independent learning curriculum; however, institutionally, they are considering it first. Fourth, the implementation of two curricula (K-13 and the Independent Learning Curriculum) produces two tendencies: k-13 is more about academic achievement, and the independent learning curriculum tends to focus more on life skill achievement.